Formulation and characterization of gastroretentive discs containing famotidine - Raval,Jignyasha Amitkumar (2011)
In this work a different type of formulation, as disc, containing a selected mucoadhesive polymer, fillers, and binders were investigated for their potential as a mucoadhesive gastroretentive delivery system to deliver famotidine in the stomach. Various types of hydrophilic diluents were evaluated for their swelling and mucoadhesive property and one (polyvinylpyrrolidone, PVP) was selected to combine with the selected mucoadhesive polymer (polyethylene oxide, PEO). Discs with different ratios of PEO and PVP were prepared and evaluated for swelling, dissolution, and mucoadhesion. The swelling property of the discs increased as the concentration of PEO was increased and also did the mucoadhesion. These discs retained their integrity and adherence onto gastric mucosa for more than 10 h under in-vitro conditions. The PEO, in combination with PVP, yielded a non-disintegrating type mucoadhesive dosage form which was suitable for gastroretentive applications to achieve the desired release profile of the drug.